Apalutamide in Patients With Metastatic Castration-Sensitive Prostate Cancer: Final Survival Analysis of the Randomized, Double-Blind, Phase III TITAN Study. Issue 20 (10th July 2021) - Chi, Kim N.; Chowdhury, Simon; Bjartell, Anders; Chung, Byung Ha; Pereira de Santana Gomes, Andrea J.; Given, Robert; Juárez Soto, Alvaro; Merseburger, Axel S.; Özgüroğlu, Mustafa; Uemura, Hirotsugu; Ye, Dingwei; Brookman-May, Sabine; et al.
Abstract : PURPOSE: The first interim analysis of the phase III, randomized, placebo-controlled TITAN study showed that apalutamide significantly improved overall survival (OS) and radiographic progression-free survival in patients with metastatic castration-sensitive prostate cancer (mCSPC) receiving ongoing androgen deprivation therapy (ADT). Herein, we report final efficacy and safety results after unblinding and placebo-to-apalutamide crossover. METHODS: Patients with mCSPC (N = 1, 052) were randomly assigned 1:1 to receive apalutamide (240 mg QD) or placebo plus ADT. After unblinding in January 2019, placebo-treated patients were allowed to receive apalutamide. Efficacy end points were updated using the Kaplan-Meier method and Cox proportional-hazards model without formal statistical retesting and adjustment for multiplicity. Change from baseline in Functional Assessment of Cancer Therapy-Prostate total score was assessed. RESULTS: With a median follow-up of 44.0 months, 405 OS events had occurred and 208 placebo-treated patients (39.5%) had crossed over to apalutamide. The median treatment duration was 39.3 (apalutamide), 20.2 (placebo), and 15.4 months (crossover). Compared with placebo, apalutamide plus ADT significantly reduced the risk of death by 35% (median OS not reached v 52.2 months; hazard ratio, 0.65; 95% CI, 0.53 to 0.79; P < .0001) and by 48% after adjustment for crossover (hazard ratio, 0.52; 95% CI, 0.42 to 0.64; P < .0001). Apalutamide plus ADT delayed second progression-free survival and castration resistance ( P < .0001 for both). Health-related quality of life, per total Functional Assessment of Cancer Therapy-Prostate, in both groups was maintained through the study. Safety was consistent with previous reports. CONCLUSION: The final analysis of TITAN confirmed that, despite crossover, apalutamide plus ADT improved OS, delayed castration resistance, maintained health-related quality of life, and had a consistent safety profile in a broad population of patients with mCSPC.